Chemical synthesis, structural and magnetic properties of Al-doped neodymium orthoferrite - Nakhaei, Mehrnoush; Nobre, Marcos A.L. [UNESP]; Khoshnoud, Davoud Sanavi; Bremholm, Martin; Khonakdar, Hossein Ali (Elsevier, 2025)
Crystalline and single phase of Al doped orthoferrite with stoichiometry NdFe1-xAlxO3 was synthesized by a hydrothermal method. The effect of Al doping on the structure features was investigated by powder X-ray diffraction (PXRD) technique. In this sense, Rietveld refinement was applied in refining the PXRD data. Scanning electron microscopy (SEM) was used to characterize the morphology. And from image analyses show a sub-micron particle size distributions for all samples. Using hydrothermal synthesis method, a micro-sized particle distribution is reached. Measurement of magnetic hysteresis loops showed that the highest coercivity (Hc) obtained was 5.2 kOe for the sample with x=2. Compared to previous results using sol-gel synthesis, the hydrothermal method used in this study showed improved magnetization properties.
Keywords: Hydrothermal; Magnetic properties; Morphology analysis; PXRD; SEM; VSM